Awakened vision as an initiatory experience in the ṭarīqa Tijāniyya. - De-Diego-González, Antonio (My University, 2024)
In Sufism, the visionary experience (ru‘ya) is one of the main methods of acquiring profound knowledge of the Reality (ḥaqīqa). For many Sufis, this experience was an initiation in which they received a hierophanic legitimation to continue and improve their spiritual path. Among the many visionary experiences in the Islamic world, those of the ṭarīqa Tijāniyya provide excellent material for analysis because they legitimised their esoteric teaching in the contemporary world. Dreams and visions have always been a key part of this ṭarīqa and have been a source of esoteric and exoteric teachings, initiations, or status legitimation within the path. The symbolic allows us to locate on the esoteric level categories such as authority or doctrine that are often located on the exoteric level. This paper presents the role of dreams and visions in the Tijāniyya and proposes a hermeneutic analysis of the awakened vision (ru‘ya fi-l yaqẓa) as an initiatory experience in two key figures: Aḥmad Tijāni (1735-1815) and Ibrāhīm Niasse (1900-1975). The first was the founder of the ṭarīqa and, according to traditional sources, received the status of the Seal of the Saints (khātm al-awliyā’) and esoteric knowledge from the Prophet Muhammad himself in an awakened vision in Algeria. The second was the initiator of the fayḍa movement and one of the most important Sufis of the twentieth century. He gained legitimacy as a Sufi master after leading a collective vision in which he transformed himself into Aḥmad Tijāni in front of his community, thus beginning a path that transformed contemporary Sufism in West Africa.
Keywords: Sufismo; Filosofía islámica; Islam; Islamic Esotericism; ENSIE (European Network for the Study of Islamic Esoteriscism); Sufism; Tijaniyya; Maghreb; West Africa; Islamic Intellectual History